2019
DOI: 10.37652/juaps.2022.171881
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol extract of Tribulus terrestris ameliorates liver of mice exposed to cadmium acetate

Abstract: Background: Tribulus terrestris is known as food supplements and therapeutic agent. Objective: This study was presented to evaluate antitoxicity of fruit alcohol extracted from Tribulus terrestris to be used against heavy metal (cadmium) in female of albino mice.Methods: Twenty mice were examined in this experiment, and they were divided into three groups. The first group was a control group, while the second group was quaffed cadmium 6mg/kg, and third group was quaffed cadmium 6mg/kg and fruit alcohol extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…After 21 days of took garlic solution plus 8.3 mg of lead chloride, the histopathological changes showed regeneration of hepatocytes appear enlarged and dark nuclei due to mitosis although the high dose of lead chloride, but others hepatocytes still swelling and loss of sinusoids which refer to regeneration which indicates the effect of garlic in returning hepatocytes to normal (Figure 7), this regeneration may be due to the presence of organ sulfur compounds in garlic that have many effect on drug metabolizing enzymes, antioxidant properties, antimicrobial, antithrombotic, hypolipidemic, antiarthritic, hypoglycemic and antitumor activity [29]. Finally, This study is in agreement with other studies that emphasize decreasing chemical toxicity by using natural products [30].…”
Section: Journal Of University Of Anbar For Pure Science (Juaps)supporting
confidence: 87%
“…After 21 days of took garlic solution plus 8.3 mg of lead chloride, the histopathological changes showed regeneration of hepatocytes appear enlarged and dark nuclei due to mitosis although the high dose of lead chloride, but others hepatocytes still swelling and loss of sinusoids which refer to regeneration which indicates the effect of garlic in returning hepatocytes to normal (Figure 7), this regeneration may be due to the presence of organ sulfur compounds in garlic that have many effect on drug metabolizing enzymes, antioxidant properties, antimicrobial, antithrombotic, hypolipidemic, antiarthritic, hypoglycemic and antitumor activity [29]. Finally, This study is in agreement with other studies that emphasize decreasing chemical toxicity by using natural products [30].…”
Section: Journal Of University Of Anbar For Pure Science (Juaps)supporting
confidence: 87%
“…23 In a study, T terrestris at the dose of 200 mg/kg protects the liver against cadmium toxicity. 24 Recently, Okorie et al 25 demonstrated the M pruriens leaf extract effect on the liver. The result showed that ALP, AST, ALT, and albumin were found to be statistically significant among the treated groups when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%